The India and César Vallejo - Bernales Albites, Enrique (2021)
In this article I will analyze Vallejo's writings in dialogue with India. This work is divided into three parts: first, I will comment on an exotic reference to India in his first book of poetry Los heraldos negros (1918). Secondly, I will examine the reception of Indian culture, as well as the works and figures of Rabindranath Tagore and Jiddu Krishnamurti, very popular and influential Indian writers of that time, expressed in their articles sent from Europe and published in Mundial, El Norte and Variedades. Finally, I will address the reception of Vallejo's work in India, in terms of the translations of his poems into the different languages of the subcontinent.